Towards OBE: A Case Study of Course Outcome (CO) and Programme Outcome (PO) Attainment for Product Design and Development Course - Akiah, Masni-Azian; Abdul Hamid, Rahimah; Othman, Mohd Shahrizan (International Organization of Scientific Research (IOSR), 2014)
The Outcome Based Education (OBE) has been one of the major concern of most academic institutions in Malaysia, especially among engineering departments since the Engineering Accreditation Council (EAC) has made it compulsory towards programme accreditation. However, various understanding towards the concept of OBE resulted to various attainment to Programme Outcome (PO) based on the Course Outcome (CO). Execution of the OBE may not be an easy matter as the mapping of the CO for each assessment may be mapped to multiple PO. This paper describe the analysis process of the CO and PO attainment for Product Design and Development subject, which is offered to all 2nd year students of Faculty of Manufacturing Engineering, Universiti Teknikal Malaysia Melaka. Two methods are incorporated, (1) direct measurement, and(2) segregated measurement. The study identified that segregated measurement are more sensitive towards identifying the issues which affect attainment of CO and PO. Issues related to non-fulfilment of either CO or PO for Product Design and Development subject can be traced to lack of awareness towards product sustainability, synthesizing product design problems and student’s attitude towards citing proper literature information throughout the development of their product.